Analysis Of Teacher Strategies In Improving Student Discipline In Grade IV Elementary School (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2026)
Discipline is an essential character value that should be developed from the elementary school level; however, discipline-related problems are still commonly found in schools. This study aims to examine teachers’ strategies in improving and maintaining discipline among fourth-grade elementary school students. A qualitative descriptive approach was employed, involving teachers as primary participants and students as supporting participants selected through purposive sampling. Data were collected through observations, interviews, and document analysis and validated using triangulation techniques. The findings indicate that teachers promote discipline through role modeling, habituation, persuasive communication, rewards, educational punishment, and consistent adaptive rule enforcement. These strategies contribute to the development of student discipline and support a conducive classroom environment.